The Philosophy of Water in Buddhaâ€™s Culture - Haudi, Haudi; Ismoyo, Tejo; Siu, Ong Cin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Water in the concept of Buddhism has a sense of Majesty, namely humility. Water has always been placed on the altar of Buddha as a means of Buddhist to always remember to teach the attitude of humble. In the Sutta Manggala was explained that when a person has a humble attitude and eager in erode greed (Kilesa), runs the sacred life and achieve enlightenment (Nibbana), is a major blessing. So we can say a must have humble character like water because it can reach the highest goals i.e. enlightenment (Nibbana). Water in Buddhist cultures are used as media treatment and endowment. Gotama Buddha in the opportunity at a time when the population of Vesali leprosy disease plagues sprinkled some holy water which has been read Paritta. Buddhism emphasizes that maintaining and preserving the water is very necessary as reflected in the Dhammapada. 49 â€œlike a bee collecting honey with no damage or harass the color and scent of flowers; so too does the wise way person move past the worldâ€. In ecosystems, the bees not only take advantage of in interest, but at the same time help the pollination. The beesâ€™ behavior gives an inspiration, how we should use the water wisely without causes the damage that would disturb the ecosystem, but it will still be able to conserve water.